HOSPITALITAS KRISTEN DAN TANTANGANNYA DI TENGAH PANDEMI COVID-19 - Daniel Fajar Panuntun; Eunike Paramita (Harmoni, 2020)
ABSTRACT The global world at the end of 2019 was shocked by a pandemic caused by the Corona Virus. Corona Virus Disease 2019 raises global concerns about the rapid and deadly spread. Indonesia has also been affected by the Covid-19 case and dated March 19, 2020 there have been 309 positive cases and still counting. The government promotes social distancing policies to reduce publicity in order to minimize the development of Covid-19. Indonesian people are responding to this recommendation, but there are some who do panic buying, persecution of health workers who have the possibility of exposure to Covid-19  and other cases that show the loss of hopitality of Indonesian citizens. This paper aims to formulate an ethical model of Christian hopitality in the midst of the Covid-19  Pandemic. This study uses a qualitative approach to theological research and social descriptive research. The results of this study consist of three main points, namely: first, Christianity must not lose empathy as an attitude of Christian hopitality in every lifetime. Second, the attitude of hopitalitas must look at the context ethically, namely the context of the distribution of Covid-19. Third, Christian hopitality has risks and impacts in the form of its implementation amid the Covid-19 pandemic. Key Words: Ethical Decisions, Hospitality, Christianity, covid-19.